The end behavior is that as the value of x increases the value of function increases.
A) We want to completely factor; f(x) = 2x² - x - 10
⇒ f(x) = 2x² - 5x + 4x - 10
⇒ 2x(x + 2) - 5(x + 2)
⇒ (2x - 5)(x + 2)
B) The x-intercept occurs at y = 0. Thus;
(2x - 5)(x + 2) = 0
x =5/2 and x = -2
C) f(x) = 2x² - x - 10
Thus, the end behavior is that as the value of x increases the value of function increases.
D) The graph steps has been attached
Read more about Function Graph at; https://brainly.com/question/14323743
#SPJ1